Atypical modulation of distant functional connectivity by cognitive state in children with Autism Spectrum Disorders - You, Xiaozhen; Norr, Megan; Murphy, Eric; Kuschner, Emily; Bal, Elgiz; Gaillard, William; Kenworthy, Lauren; Vaidya, Chandan J. (Frontiers in Human Neuroscience, 2013)
We examined whether modulation of functional connectivity by cognitive state differed between pre-adolescent children with Autism Spectrum Disorders (ASD) and age and IQ-matched control children. Children underwent functional magnetic resonance imaging (fMRI) during two states, a resting state followed by a sustained attention task. A voxel-wise method was used to characterize functional connectivity at two levels, local (within a voxel’s 14 mm neighborhood) and distant (outside of the voxel’s 14 mm neighborhood to the rest of the brain) and regions exhibiting Group X State interaction were identified for both types of connectivity maps. Distant functional connectivity of regions in the left frontal lobe (dorsolateral [BA 11, 10]; supplementary motor area extending into dorsal anterior cingulate [BA 32/8]; and premotor [BA 6, 8, 9]), right parietal lobe (paracentral lobule [BA 6 ]; angular gyrus [BA 39/40]), and left posterior middle temporal cortex (BA 19/39) showed a Group X State interaction such that relative to the resting state, connectivity reduced (i.e., became focal) in control children but increased (i.e., became diffuse) in ASD children during the task state. Higher state-related increase in distant connectivity of left frontal and right angular gyrus predicted worse inattention in ASD children. Two graph theory measures (global efficiency and modularity) were also sensitive to Group X State differences, with the magnitude of state-related change predicting inattention in the ASD children. Our results indicate that as ASD children transition from an unconstrained to a sustained attentional state, functional connectivity of frontal and parietal regions with the rest of the brain becomes more widespread in a manner that may be maladaptive as it was associated with attention problems in everyday life.